2021
DOI: 10.3390/ijerph18168606
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Self-Directed Violence: Understanding Intention to Help and Helping Behaviors among Adolescents and Emerging Adults

Abstract: Exposure to self-directed violence (SDV) is a public health issue. Prevention trains third parties to identify SDV risk and provide help. However, we know little about the range of help provided to those who engage in SDV. The current study used a cross-sectional online survey of 1031 adolescents and emerging adults to learn about their SDV exposure, intent and attempts to help, and barriers to helping. Most participants reported SDV exposure, commonly by a peer, and provided help. Regression analyses showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…In addition, 15 studies reported on emotional support, suggesting that this is also a crucial aspect of young‐people's help‐giving processes. Emotional support was described as using caring words to express concern and providing reassurance, listening non‐judgementally, and discussing the mental health problem experienced by the peer (Banyard et al, 2021; Rodgers et al, 2019; Smart, 2010; Yap et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, 15 studies reported on emotional support, suggesting that this is also a crucial aspect of young‐people's help‐giving processes. Emotional support was described as using caring words to express concern and providing reassurance, listening non‐judgementally, and discussing the mental health problem experienced by the peer (Banyard et al, 2021; Rodgers et al, 2019; Smart, 2010; Yap et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Typically, studies reported low levels of confidence when helping a peer through mental health crises. Banyard et al (2021) and Lavis and Winter (2020) found that young people helping in crisis situations…”
Section: Confidence In Helpingmentioning
confidence: 99%
See 1 more Smart Citation
“…Community suicide interventions aim to encourage bystander action in the event of a crisis. The difficulty with bystander action is that many people are usually present in an emergency, which makes it difficult to determine who is most responsible to act [ 13 ]. A recent study found that one of the biggest reasons people do not intervene in a suicide attempt is that they thought someone else closer to the individual would take action [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study found that one of the biggest reasons people do not intervene in a suicide attempt is that they thought someone else closer to the individual would take action [ 14 ]. Inaction resulting from diffusion of responsibility is known as the bystander effect [ 13 ]. The bystander intervention model (BIM) is a potential mechanism for overcoming the bystander effect.…”
Section: Introductionmentioning
confidence: 99%